Pengaruh Penggunaan E-Wallet terhadap Perilaku Konsumtif Mahasiswa dengan Literasi Keuangan sebagai Variabel Intervening - Rizky Amelia Putri; Adria Wuri Lastari; Mulia Inda Purwati (ARZUSIN, 2026)
The development of e-wallet use has changed students’ transaction patterns through payment convenience, promotions, and digital financial features, but studies examining the effect of e-wallet use on consumptive behavior with financial literacy as a mediating variable remain limited. This study aims to analyze the effect of e-wallet use on consumptive behavior and financial literacy, the effect of financial literacy on consumptive behavior, and the mediating role of financial literacy in the relationship between e-wallet use and students’ consumptive behavior. This study used a quantitative approach with a causal associative design. The sample consisted of 56 students of the Management Study Program, Faculty of Economics, Universitas Adiwangsa Jambi, who were selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS. The results show that e-wallet use has a positive and significant effect on consumptive behavior and financial literacy. Financial literacy also has a positive and significant effect on consumptive behavior and partially mediates the effect of e-wallet use on students’ consumptive behavior. The conclusion of this study emphasizes that e-wallet use contributes to the formation of students’ consumptive behavior, both directly and through financial literacy. The implications of this study indicate that improving financial literacy needs to be balanced with self-control and the consistent application of financial management so that the use of digital financial services becomes wiser and more responsible.